Removal of a Missing Intrauterine Device Via Laparotomy after 28 Years of Insertion: A Case Report - Aktoz, Fatih; Gunes, Ali Can; Kuru, Oguzhan; Tuncer, Zafer Selcuk (Gynecology Obstetrics & Reproductive Medicine, 2019)
Intrauterine device is one of the most preferred contraceptive methods. Rare complications such as uterine perforation were getting more common due to increased use of intrauterine device and could be seen either with mild manifestations or serious cases like bladder or intestinal damage. A 48-year-old patient who is consulted to our clinic because of a missed copper intrauterine device was presented. The intrauterine device was inserted 28 years ago, detected in pelvis incidentally by x-ray and extracted via laparotomy. Although device has been in abdomen for nearly three decades, we did not see any serious reaction or adhesion during surgery. Management of a patient with intrauterine device should be done carefully and following the instructions before insertion, regular examination at every visit are important.